A new species of Dasyhelea Kieffer (Diptera: Ceratopogonidae) from Brazilian Amazonia - Díaz, Florentina; Ronderos, María Marcela; Spinelli, Gustavo Ricardo; Ferreira-Keppler, Ruth Leila; Torreias, Sharlene Roberta da Silva (Zootaxa, 2013)
A new species from Manaus, Amazonas, Brazil, Dasyhelea eloyi Díaz & Ronderos, is described, illustrated and photomicrograph as larva, pupa and male and female adults based on examination with binocular and scanning electron microscopes. This new species, a typical member of the Dasyhelea grisea species group, is compared with the most similar congeners D. necrophila Spinelli & Rodríguez and the Nearctic D. pseudoincinsurata Waugh & Wirth. Copyright © 2013 Magnolia Press.
Keywords: Anatomy And Histology; Animals; Animals Dispersal; Animals Structures; Body Size; Ceratopogonidae; Classification; Female; Growth, Development And Aging; Male; Animals Distribution; Animals Structures; Animal; Body Size; Ceratopogonidae; Female; Male